Consumer purchase behavior for meat products in Davao City - Bangcaya, Angel Mae P.
Meat remains as one of the most consumed commodity throughout the world and it has long occupied a special place in the food intake of consumers. In the Philippines, meat volumes are predicted to increase because of the rapid increase in population and the growth of the food service sector in the country. Understanding the purchase behavior of consumers for meat industry. Thus, this study aimed to assess the purchase behavior of consumers towards the three major meat products consumed and produced in the country namely beef, dressed chicken and pork. Decision makers of the household purchase were the key respondents of this study. Based on the results, the availability of fresh products and the cleanliness of the area were very important for consumers on their choice for place of purchase. Meanwhile, accessibility was found to be more important for income class C and DE than for income class AB. In terms of the consumers rating for meat attributes, it showed that color was of highest consideration as it is the primary indication of product freshness. On the other hand, results of the logistic regression model showed that beef purchase choice was significantly affected by average monthly income, working status, household size, number employed household members, and number of children in the household. For chicken and pork purchase choice, area and number of employed household members and religion, were the factors significantly affecting consumer purchase decision respectively.